2000
DOI: 10.1161/01.hyp.36.5.872
|View full text |Cite
|
Sign up to set email alerts
|

Subpressor Dose of L-NAME Unmasks Hypertensive Effect of Chronic Hyperinsulinemia

Abstract: Abstract-We previously found that chronic exogenous hyperinsulinemia without sugar supplementation does not elevate blood pressure. This may be partially explained by the ability of insulin to release nitric oxide and cause vasodilatation.To test this hypothesis, we studied 4 groups of rats: 9 rats (body weight, 213Ϯ14 g) treated with a gradual increase of a sustained-release subcutaneous insulin pellet; 9 rats (body weight, 213Ϯ9 g) treated with N G -nitro-L-arginine methyl ester (L-NAME) in drinking water 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…46 Another possibility, based on rat studies, is that chronic hyperinsulinemia may not universally affect BP but may cause hypertension when endothelial dysfunction is present. 47 The relationship between capillary function ⁄ density and hypertension, IS, and EF is in need of further exploration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…46 Another possibility, based on rat studies, is that chronic hyperinsulinemia may not universally affect BP but may cause hypertension when endothelial dysfunction is present. 47 The relationship between capillary function ⁄ density and hypertension, IS, and EF is in need of further exploration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat surprising, considering that insulin increases vascular NO production, although such an effect would not be expected to have been confined to the hindquarters (Hilzenrat et al, 2001). But, although an NO-dependent component of the vasodilator action of insulin is widely acknowledged (see Hsueh and Law, 1999, for review; Bursztyn et al, 2000;Molinari et al, 2001), there is evidence that the vasodilator action of thiazolidenediones on rat coronary vessels (Uchida et al, 2000) and the human forearm (Fujishima et al, 1998) is NO-independent. In fact, there is evidence that PPAR-␥ ligands may suppress inducible nitric-oxide synthase expression while increasing heme oxygenase-1 expression in rat glial cells (Kitamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia was implemented by following a previously published procedure (6). Briefly, rats received a 2-mm segment of a 7-mm blank or sustained-release bovine insulin-releasing pellet (the expected delivery rate of insulin was 0.6 U/day for Ͼ40 days as indicated by the manufacturer of the pellet) under short-term isoflurane anesthesia (model 100 vaporizer, Surgivet).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies (4,27) have reported an association between experimental hyperinsulinemia and hypertension or hypertriglyceridemia. We used a model of insulin infusion in the rat on the basis of a report (6) indicating that the use of an implantable insulin-impregnated pellet, in two stages, induces modest hyperinsulinemia without eliciting significant hypertension or hypertriglyceridemia. As shown in Fig.…”
Section: Infusion Of Insulin Induced Modest Hyperinsulinemia But Notmentioning
confidence: 99%